Efficient multicore-aware parallelization strategies for iterative stencil computations - Eitzinger, Jan; Wellein, Gerhard; Hager, Georg (Journal of Computational Science, 2011)
Stencil computations consume a major part of runtime in many scientific simulation codes. As prototypes for this class of algorithms we consider the iterative Jacobi and Gauss-Seidel smoothers and aim at highly efficient parallel implementations for cache-based multicore architectures. Temporal cache blocking is a known advanced optimization technique, which can reduce the pressure on the memory bus significantly. We apply and refine this optimization for a recently presented temporal blocking strategy designed to explicitly utilize multicore characteristics. Especially for the case of Gauss-Seidel smoothers we show that simultaneous multi-threading (SMT) can yield substantial performance improvements for our optimized algorithm on some architectures. © 2011 Elsevier B.V.
UnivIS-Import:2015-03-09:Pub.2011.tech.IMMD.phleir._effic
Keywords: Multicore; Simultaneous multi-threading; Spatial blocking; Stencil computations; Temporal blocking; Wavefront parallelization